2017
DOI: 10.1016/j.chroma.2017.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolysis-gas chromatography–isotope ratio mass spectrometry for monitoring natural additives in polylactic acid active food packages

Abstract: Compound-specific isotope analysis (CSIA) usually requires preparative steps (pretreatments, extraction, derivatization) to get amenable chromatographic analytes from bulk geological, biological or synthetic materials. Analytical pyrolysis (Py-GC/MS) can help to overcome such sample manipulation. This communication describe the results obtained by hyphenating analytical pyrolysis (Py-GC) with carbon isotope-ratio mass spectrometry (IRMS) for the analysis of a polylactic acid (PLA) a based bio-plastic extruded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…After 2 months no further significant changes occurred in the spectra (Correa et al, 2008). Finally, a further methodology used to follow the evolution of the spectrum of the tested material is pyrolysis–gas chromatography–isotope ratio mass spectrometry, used to identify particular additives in PLA (Llana-Ruíz-Cabello et al, 2016, 2017) through the isotope ratio typical of each material and to identify PE in blends and carrier bags made from biodegradable polymers PBAT and PLA (Rizzarelli et al, 2016).…”
Section: Methodologies To Monitor Biodegradation Of Bioplasticsmentioning
confidence: 99%
“…After 2 months no further significant changes occurred in the spectra (Correa et al, 2008). Finally, a further methodology used to follow the evolution of the spectrum of the tested material is pyrolysis–gas chromatography–isotope ratio mass spectrometry, used to identify particular additives in PLA (Llana-Ruíz-Cabello et al, 2016, 2017) through the isotope ratio typical of each material and to identify PE in blends and carrier bags made from biodegradable polymers PBAT and PLA (Rizzarelli et al, 2016).…”
Section: Methodologies To Monitor Biodegradation Of Bioplasticsmentioning
confidence: 99%
“…Py-GC/MS is now a recognized method for the fast identification and semi-quantification of organic contaminants, including OPAs (Table 1). It provides a well-known advantage: it does not require sample pretreatment, such as SE (Llana-Ruiz-Cabello et al, 2017). Analysis can be carried out by simply placing a suitable amount of weighed out sample directly in a pyrolysis sample cup, thereby limiting background contamination (Dekiff et al, 2014;Fries et al, 2013;Kudo et al, 2019;Terán et al, 2009).…”
Section: Onmentioning
confidence: 99%
“…The analysis of OPAs has grown in importance over the past few decades since the use of certain additives has become a controversial issue as some of them were found to be toxic to human (Yanagisawa et al, 2018). Compared with other detection methods, such as liquid chromatography coupled with mass spectrometry (LC/MS) or GC/MS analysis with a solvent extraction (SE) step, Py-GC/MS has the advantage of having a relatively easy and fast sample preparation (Kim et al, 2016;Llana-Ruiz-Cabello et al, 2017;Maruyama et al, 2015;Odermatt et al, 2003;Yanagisawa et al, 2018). This technique has been applied to the qualitative and semi-quantitative analysis of a large variety of additives in polymers.…”
Section: Introductionmentioning
confidence: 99%
“…As global bioplastic production and consumption continue to increase, there is growing concern regarding the potential for environmental pollution as well as the release of associated harmful chemicals (particularly additives) from micro-bioplastics in the environment. ,,, Understanding the fate of micro-bioplastics in different environmental compartments is therefore of utmost importance. The occurrence of micro-bioplastic residues (i.e., PCL, PLA, PBS, PHB, starch-based plastic (SBP)) in environmental samples, specifically in air, soil, ice cores, WWTP effluents, and rivers , and the tissues of aquatic organisms have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, pyrolysis–gas chromatography–mass spectrometry (Pyr-GC/MS), an emerging technique in environmental polymer analysis, has been shown to be a suitable tool for the simultaneous identification and mass quantification of several synthetic polymers in environmental samples. Pyr-GC/MS capture size ranges of both micro (particles <5 mm) and nanoplastics (particles <1 μm), and have the ability to provide internal standard corrected concentrations. ,, Pyr-GC/MS can also help reduce preparative manipulation of samples, requiring relatively small sample sizes with little or no preparation, making it a convenient method for inexpensive and relatively rapid routine analyses. , For bioplastics, Pyr-GC/MS has been shown to be a suitable tool for the identification and structural composition analysis of the thermal degradation products of bioplastics such as PLA, , PBS, , PHA, and PCL, either as a virgin material or with variable quantities of additives. , However, the technique has primarily been used qualitatively for the identification/confirmation of polymer content and has rarely been used for the quantification of micro-bioplastics in environmental samples. In our previous studies, we have demonstrated that pressurized liquid extraction (PLE) at high temperature and pressure, coupled with Pyr-GC/MS, is a promising technique for the extraction and analysis (mass quantification) of numerous plastics (polyethylene (PE), poly­(methyl methacrylate) (PMMA), polycarbonate (PC), poly­(vinyl chloride) (PVC), polystyrene (PS), polypropylene (PP), and poly­(ethylene terephthalate) (PET)) from biosolids, road dust, rice, medium to high lipid foods, and seafood samples. ,,,,,, We, therefore, hypothesize that PLE combined with Pyr-GC/MS has the potential to efficiently extract and quantify micro-bioplastics in complex environmental samples.…”
Section: Introductionmentioning
confidence: 99%